Formação de redes sociais e inovação : um estudo nas empresas incubadas do Parque Tecnológico Itaipu - Souza, Márcia Cristina David de (2011)
The research on the formation and evolution of social networks and how they affect the organizations has gained attention in the studies of business administration. In these researches, social networks are identified as a major factor in the process of innovation generation. Thus, in order to understand how social networks influence innovation, a possible approach is to evaluate social networks through the formation and evolution of their relationships. This is the context of the present study, which aims to analyze how the formation and evolution of social networks influence innovation in three companies incubated in the Santos Dumont Business Incubator, part of the Itaipu Technological Park, located in Foz do Iguaçu, PR. To achieve the proposed objective, we performed a multiple case study on three companies in different incubation stages, with longitudinal cut. Two data collection were conducted, with an interval of six months between them, using semi-structured interviews as instruments for data collection, taken from incubated companies managers and representatives of the incubator. For the interpretation of the collected data, it was chosen the content analysis method with support of the Atlas.ti software. Among the findings of this study, it is worth mentioning the identification of the influence of social networks, in their formation and evolution, on the adopted innovation and its progression for three incubated companies of the ESDI, and the particular characteristics of the formation and evolution of these networks besides their impact on the search for resources and information for the company. The research also highlights the role of the incubator as a mediator of relationships which provide resources and relevant information sources to the incubated companies.